2001
DOI: 10.1038/sj.sc.3101119
|View full text |Cite
|
Sign up to set email alerts
|

Bowel dysfunction following spinal cord injury

Abstract: Study Design: Review. Objectives: To outline the present knowledge of bowel dysfunction following spinal injury, and look at future directions of management and research. Setting: Spinal Unit and Colorectal Unit, Christchurch, New Zealand. Methodology: Review. Results: The underlying physiology of colorectal motility and defecation is reviewed, and consequences of spinal cord injury on defecation are reported. A discussion of present management techniques is undertaken and new directions in management and rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 40 publications
2
115
0
1
Order By: Relevance
“…13 A previous study found that patients with higher tetraplegia had the highest prevalence of bowel problems compared with patients with lower paraplegia. 14 Lynch et al 15 also reported that the level of the spinal cord lesion determines the effect on colonic motility, and cervical injuries can result in more remarkable constipation, abdominal distention and discomfort. From the results of our study, we can clearly see that cervical and thoracic level of injury carry a higher risk of severe NBD than lumbar level injury (OR ¼ 10.5 and 7.1, respectively) and the severity of bowel dysfunction is strongly associated with the level of cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A previous study found that patients with higher tetraplegia had the highest prevalence of bowel problems compared with patients with lower paraplegia. 14 Lynch et al 15 also reported that the level of the spinal cord lesion determines the effect on colonic motility, and cervical injuries can result in more remarkable constipation, abdominal distention and discomfort. From the results of our study, we can clearly see that cervical and thoracic level of injury carry a higher risk of severe NBD than lumbar level injury (OR ¼ 10.5 and 7.1, respectively) and the severity of bowel dysfunction is strongly associated with the level of cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 0 to 63, with higher scores indicating a greater level of a depressive mood. The total score can be further categorized into four grades: normal (0-13); mild depression (14)(15)(16)(17)(18)(19); moderate depression (20-28); and severe depression (29-63).…”
Section: Methodsmentioning
confidence: 99%
“…Moderately invasive, use of rectal stimulant/ osmotic laxative, can result in prolonged reflex rectal activity leading to incontinence, abdominal cramping, irritation of rectal mucosa, can result in soiling because of retention of melted suppositories. 6 Manual evacuation Mechanical removal of stool from the bowel using a digit.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…[3][4][5] Neurogenic bowel dysfunction can result in considerable morbidity, such as autonomic dysreflexia, impaction, hemorrhoids, abdominal pain, rectal bleeding, rectal prolapse, anal fissure, bloating, nausea, constipation and prolonged evacuation. 1,3,4,6,7 Bowel management programs are based on regular routine, dietary manipulation, laxatives, digital and pharmacological rectal stimulation, manual evacuation of stool and assistive interventions such as abdominal massage. There is little evidence to support these interventions individually or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 In rehabilitation centres, nurses care for the bowel management of patients with SCI and initiate a bowel management program. 21 The aim of such programs is to eliminate faecal incontinence or other complications 3,19 and to evacuate stool at a regular, predictable time 14,19 within 60 min. 7 The interventions include the manual removal of stool 11,15,17,19,22 for patients with an areflexic bowel as well as techniques like digital stimulation 11,15,22 and suppositories 11,15,22 for patients with a reflexic bowel to initiate reflex peristalsis, 14 frequency, 14 timing of bowel evacuation, 11,22 and the usage of oral laxatives.…”
Section: Introductionmentioning
confidence: 99%